Synthesis and Crystal Structure of New Pb(II) Complex with p-tert-Butyl Benzoic Acid - Wang, Wen-Jian; Wang, Hong-Liang; Bi, Jian-Hong (Asian Journal of Chemistry, 2015)
A new Pb(II) complex of formula [Pb(PTBA)2H2O] (PTBA = p-tert-butyl benzoic acid) has been synthesized and the crystal structure was characterized by single crystal X-ray diffraction. The complex crystallizes in the system and belongs to space group: triclinic, P-1 with a = 6.6964(7)Å, b = 12.5782(12)Å, c = 13.9056(14)Å, a = 91.8640(10)º, b = 101.141(2)º, g = 97.5670(10)º, V = 1137.1(2)Å3, Z = 2, Dc = 1.693 Mg/cm3, Mr = 579.63, μ(moKo) = 7.445 mm-1, F(000) = 564. R = 0.0282 and wR = 0.0575 for 3943 observed reflections with I >s(I). The crystal structure analysis indicates that the Pb(II) ion is five-coordinated by two PTBA ligand molecules and one water molecule.